Geographies of violence in Jerusalem: The spatial logic of urban intergroup conflict. (September 2018) - Rokem, Jonathan; Weiss, Chagai M.; Miodownik, Dan
Abstract: This paper assesses how spatial configurations shape and transform individual and collective forms of urban violence, suggesting that geographies of urban violence should be understood as an issue of mobility. We document and map violent events in Jerusalem, assessing the possible impact of street patterns: segmenting populations, linking populations, and creating spaces for conflict between the city's Jewish and Palestinian populations. Using space syntax network analysis, we demonstrate that, in the case of Jerusalem, street connectivity is positively associated with individual violence yet negatively associated with collective violence. Our findings suggest that understanding the logic of urban intergroup violence requires us to pay close attention to local urban morphology and its impact on intergroup relations in ethnically divided and heterogeneous environments. Highlights: The geographies of urban intergroup violence should be understood as an issue of connectivity and mobility in space. Individual and collective forms of violence manifest themselves differently and are driven by geospatial factors. Space syntax analyses can illuminate our understanding of urban violence from a geographical perspective. Individuals implementing intergroup violence rely on connective locations to provide accessible targets. The spatial logic of intergroup violence is evident in Jerusalem, with its potent ethnonational residential segregation.